Paglipas ng dilim Cultural Center of the Philippines. - Palma, Precioso; Ignacio, Leon (CCP sarswela series, 1992)
Tanghalang Pilipino's 1991 production of Paglipas ng Dilim. A sarswela or comedy play about values written by Precioso Palma in 1920 and music by Leon Ignacio.